PROFESSOR RAMZAEV P.V. – SCIENTIST OF WORLDWIDE REPUTATION - V. V. Omelchuk; G. V. Arkhangelskaya; I. A. Zvonova (Радиационная гигиена)
An  article  provides  information  that  reveals  the  international  aspects  of  professor  P.V.  Ramzaev activities. The article specifies the main scientific achievements at the international level, provides references and information on presentations at various international scientific meetings.